2021
DOI: 10.3390/healthcare9010073
|View full text |Cite
|
Sign up to set email alerts
|

Developing the eMedical Student (eMS)—A Pilot Project Integrating Medical Students into the Tele-ICU during the COVID-19 Pandemic and beyond

Abstract: The COVID-19 pandemic has accelerated the demand for virtual healthcare delivery and highlighted the scarcity of telehealth medical student curricula, particularly tele-critical care. In partnership with the Penn E-lert program and the Department of Anesthesiology and Critical Care, the Perelman School of Medicine (PSOM) established a tele-ICU rotation to support the care of patients diagnosed with COVID-19 in the Intensive Care Unit (ICU). The four-week course had seven elements: (1) 60 h of clinical engageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 9 publications
0
30
0
1
Order By: Relevance
“…Adding to previous reviews, we found reports using telemedicine to overcome the challenges in clinical education amidst the pandemic disruption ( Table 2 ). 17 papers [ 8 , 9 , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ] described the use of telemedicine as an educational tool mostly for clerkship rotations but three also included pre-clinical year students. Whilst telemedicine was mainly implemented in university hospitals, six programs were also executed in the community.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Adding to previous reviews, we found reports using telemedicine to overcome the challenges in clinical education amidst the pandemic disruption ( Table 2 ). 17 papers [ 8 , 9 , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ] described the use of telemedicine as an educational tool mostly for clerkship rotations but three also included pre-clinical year students. Whilst telemedicine was mainly implemented in university hospitals, six programs were also executed in the community.…”
Section: Resultsmentioning
confidence: 99%
“…5 ). Practice guidelines [ 11 , 12 , 20 , 22 ] and training for faculty and students were provided [ 10 , 14 , 16 , 18 , 20 , 22 , 24 ] prior to encountering patients over the telehealth platform. In-advance informed consent from the patients were obtained and screening took place to ensure patients had the appropriate virtual interfaces [ 18 , 19 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations